Intersubiektywne uznanie, czyli personalizacja podmiotu - Byczyński, Marcin (Filozofia Publiczna i Edukacja Demokratyczna, 2014)
The aim of this article is to clarify the meaning of the concept of recognition in Axel Honneth’s theory of recognition. The main object of interest will be the differences between, what Honneth calls the basic form of recognition and recognition which he describes as a relation. Presented considerations will become premises for such an interpretation of theory of recognition, which differentiates at least between two meanings of the term recognition: first, as a subjective attitude, second, as a relation (which is more adequate interpretation). The indicated differences might be important for in-depth analyses of the theory of recognition, especially considering Honneth’s point of view – more formal approach presented in The Struggle for Recognition, to his analyses of democratic ethical life in his latest book Das Recht Der Freicheit.